Pengembangan Manajemen Lembaga Pendidikan Islam di Era Disrupsi - Mustopa, Ali Mustopa Yakub Simbolon; Iswantir, Iswantir (LP2M Universitas Islam Ahmad Dahlan, 2023)
This research is structured to describe and examine the management development of Islamic educational institutions in the Disruption Era. This research method is qualitative with a library research approach, reference sources come from books, scientific articles through Google Scholar. The study's findings show that the massive shift from manual to digital in the Disruption Era presents a challenge for the growth of Islamic educational institutions, but it also presents opportunities due to the availability of digital-based (online) management features that are designed to improve educational services. Designing a plan to be ready to compete and survive in this era is very important by optimizing resources. The approach used by Islamic educational institutions is a model for creating better human beings morally and innovatively. Therefore, there are four strategies that need to be prepared, including: 1) Getting out of the comfort zone, 2) Prioritizing offering useful and influential activities, 3) Receiving and offering quality feedback, 4) Forming a mental model of someone who has special technical expertise. Therefore, Islamic Education Institutions obtain solutions that show presence and readiness to face current challenges.